Perceptual organization in schizophrenia spectrum disorders empirical research and theoretical implications. [article]. - Uhlhaas, P.J.
The research into perceptual organization in schizophrenia spectrum disorders has found evidence for and against a perceptual organization deficit and has interpreted the data from within several different theoretical frameworks. A synthesis of this evidence, however, reveals that this body of work has produced reliable evidence for deficits in schizophrenia, as well as for the clinical, stimulus, and task parameters associated with normal and abnormal performance. Recent models of cognition have also advanced understanding of the underlying pathophysiological processes of perceptual organization dysfunction in schizophrenia spectrum disorders. These suggest that deficits in perceptual organization may be one manifestation of a wider disturbance in the integration of contextually related information across space and time. -- (from the author)